2009
DOI: 10.1080/03088830903346061
|View full text |Cite
|
Sign up to set email alerts
|

An econometric analysis for container shipping market

Abstract: This article presents an econometric analysis for the fluctuation of the container freight rate due to the interactions between the demand for container transportation services and the container fleet capacity. The demand is derived from international trade and is assumed to be exogenous, while the fleet capacity increases with new orders made two years before, proportional to the industrial profit. Assuming the market clears each year, the shipping freight rate will change with the relative magnitude of shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Broadly speaking, two approaches have been developed. First, many researchers have focused on modelling the demand and supply for transportation using the structural model [12][13][14][15]. Second, in recent years, inspired by developments in financial economics, the focus has been on modelling the freight rate or freight derivatives directly in a stochastic-statistical model [5,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly speaking, two approaches have been developed. First, many researchers have focused on modelling the demand and supply for transportation using the structural model [12][13][14][15]. Second, in recent years, inspired by developments in financial economics, the focus has been on modelling the freight rate or freight derivatives directly in a stochastic-statistical model [5,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He concluded that it is difficult to forecast freight rates in the long term because of the unpredictability of factors influencing these rates. Luo, Fan [15] developed an econometric model to analyse the fluctuation of the container freight rate and fleet capacity. They estimated the Simultaneous Equations Model using three-stage least squares, demonstrating a high degree of accuracy for insample and out-sample prediction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are some studies on containership investments (Fan and Luo 2013;Fan and Yin 2015;Luo et al 2009) from either firm level or industry level perspective due to firm-level data availability for container shipping companies. However, the studies in bulk shipping are confronted with low availability of firm-level data.…”
Section: Overview Of Ship Investmentsmentioning
confidence: 99%
“…Along with the increase in investment, container shipping market has recently received increasing attention from scholars. The study of Luo, Fan and Liu (Luo et al 2009) analysed the container freight rate fluctuation attributable to the interactions of demand for container transportation services and the container fleet capacity. They empirically evaluated demand increase and fleet capacity increase which will lead to freight rate increase.…”
Section: Container Shipping Marketmentioning
confidence: 99%